2014
DOI: 10.1371/journal.pone.0099159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tonic Pain on Motor Acquisition and Retention while Learning to Reach in a Force Field

Abstract: Most patients receiving intensive rehabilitation to improve their upper limb function experience pain. Despite this, the impact of pain on the ability to learn a specific motor task is still unknown. The aim of this study was to determine whether the presence of experimental tonic pain interferes with the acquisition and retention stages of motor learning associated with training in a reaching task. Twenty-nine healthy subjects were randomized to either a Control or Pain Group (receiving topical capsaicin crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 48 publications
5
62
1
Order By: Relevance
“…The fact that participants of each group adopted different motor strategies during the locomotor adaptation emphasises the fact that motor skills can be acquired differently with pain although the task goal may still be reached. Previous studies have shown reorganisation of muscle activity with pain or alterations in kinematics while maintaining the global motor performance intact in line with changes in motor strategy observed in the present study [9, 24, 25]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The fact that participants of each group adopted different motor strategies during the locomotor adaptation emphasises the fact that motor skills can be acquired differently with pain although the task goal may still be reached. Previous studies have shown reorganisation of muscle activity with pain or alterations in kinematics while maintaining the global motor performance intact in line with changes in motor strategy observed in the present study [9, 24, 25]. …”
Section: Discussionsupporting
confidence: 91%
“…In the central nervous system (CNS), sensory information available during motor practice would be associated with the goal of the task and the state of the motor system to form a representation of the motor skill, which would contribute to the specificity of practice effect [14, 15]. Another aspect that might impact the ability to transfer a motor skill from a “pain context” to a “pain-free context” is the fact that pain has been reported to influence motor strategies used during motor adaptation tasks, even when the global performance itself is not affected [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, pain stimulants have been found to interfere with FF control in preparation for movement. This minimizes trajectory corrections in the FB control period 11. Considering that we observed impaired motor control during the FF and FB periods in our participant, pathological pain might first disrupt precise goal-directed movements during the FB control period.…”
Section: Discussionmentioning
confidence: 70%
“…Movement disorders such as Parkinson’s disease and cerebellar ataxia disturb goal-directed reaching movement 8,9. Acute experimental pain in healthy subjects has also been found to disturb goal-directed reaching movement 10,11. However, few studies have investigated reaching control in patients with chronic pain in an upper limb.…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, pain has been shown to directly interfere with sensorimotor functions, such as the capacity to learn locomotor 9 and upper limb motor 10 tasks. As such, simultaneous treatment of motor functions and pain would be preferred over conventional treatment, that is suboptimal as evidenced by the high prevalence of chronic pain.…”
Section: Introductionmentioning
confidence: 99%